Measuring system for testing electrical parameters of EMCCDs of various formats - Zabudsky, V.; Golenkov, O.; Rikhalsky, O.; Reva, V.; Korinets, S.; Dukhnin, S.; Mytiai, R. (Технология и конструирование в электронной аппаратуре, 2019)
This article describes the developed equipment that allows measuring the photoelectrical parameters of multielement photodetectors, specifically various formats of EMCCD (electron multiplying charge-coupled device) chips. The authors present the measuring techniques and test results on dark currents, output amplifier sensitivity, charge transfer efficiency, charge capacity and other parameters. The studies were conducted, both on the wafer and in the body, on samples of the following formats: 576×288, 640×512, 768×576, 1024×1024, and 1280×1024. В данной статье описывается разработанное оборудование, позволяющее измерять фотоэлектрические параметры многоэлементных фотоприемников, в частности, различных форматов микросхем ПЗСЭУ (приборы с зарядовой связью и электронным умножением). Представляны методы измерения и результаты испытаний на темновые токи, чувствительность выходного усилителя, эффективность переноса заряда, зарядную емкость и другие параметры. Исследования проводились на образцах следующих форматов: 576×288, 640×512, 768×576, 1024×1024 и 1280×1024, как на пластине, так и в корпусе. В даній статті описано розроблену вимірювальну систему, що дозволяє досліджувати фотоелектричні параметри багатоелементних фотоприймачів, зокрема ПЗЗЕМ різних форматів. Представлено методики та результати вимірювань темнових струмів, чутливості вихідного підсилювача, ефективності передачі заряду, зарядової ємності та інших параметрів. Дослідження проводилися на зразках формату 576×288, 640×512, 768×576, 1024×1024, 1280×1024 як на пластинах, так і в корпусах.